THE INFLUENCE OF AUGMENTED REALITY MEDIA TO IMPROVE UNDERSTANDING CONCEPTS IN SOCIAL STUDIES LEARNING IN ELEMENTARY SCHOOLS - Nur Fajrina; Ahmad Arifuddin; Heru Mudiyanto (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2025)
This research aims to determine the effect of using augmented reality media on increasing understanding of social studies learning concepts in elementary schools. This research is a quantitative research with a quasi-experimental design, namely a type of non equivalent control group design. The data collection techniques used are observation techniques, tests and questionnaires. Meanwhile, the sampling technique used saturated sampling with a sample size of 58 students. In addition, the data used in the research were analyzed using observation and questionnaire data analysis test, the N-Gain test, and the non-parametric hypothesis test, namely the Mann Whitney U test. The results of non-parametric hypothesis testing with the Mann Whitney U test, it shows that the significance value of 0.032 is smaller than 0.05, so Ha is rejected and H0 is accepted. This means that there is a significant influence between the use of augmented reality media on increasing understanding of social studies learning concepts in elementary schools.